Late Cenozoic Denudation and Topographic Evolution History of the Lhasa River Drainage in Southern Tibetan Plateau: Insights From Inverse Thermal History Modeling - Cai, Dongxu; Wang, Xianyan; Li, Guangwei; Zhu, Wenbin; Lu, Huayu (Frontiers in Earth Science, 2021)
The interaction of surface erosion (e.g., fluvial incision) and tectonic uplift shapes the landform in the Tibetan Plateau. The Lhasa River flows toward the southwest across the central Gangdese Mountains in the southern Tibetan Plateau, characterized by a low-relief and high-elevation landscape. However, the evolution of low-relief topography and the establishment of the Lhasa River remain highly under debate. Here, we collected thermochronological ages reported in the Lhasa River drainage, using a 3D thermokinematic model to invert both late Cenozoic denudation and relief history of the Lhasa River drainage. Our results show that the Lhasa River drainage underwent four-phase denudation history, including two-stage rapid denudation at ∼25–16 Ma (with a rate of ∼0.42 km/Ma) and ∼16–12 Ma (with a rate of ∼0.72 km/Ma). In the latest Oligocene–early Miocene, uplift of the Gangdese Mountains triggered the rapid denudation and the formation of the current main drainage of the Lhasa River. In the middle Miocene, the second stage of the rapid denudation and the high relief were associated with intense incision of the Lhasa River, which is probably due to the enhanced Asian summer monsoon precipitation. This later rapid episode was consistent with the records of regional main drainage systems. After ∼12 Ma, the denudation rate decreases rapidly, and the relief of topography in the central Gangdese region was gradually subdued. This indicates that the fluvial erosion resulting from Asian monsoon precipitation increase significantly impacts on the topographic evolution in the central Gangdese region.